1982
DOI: 10.1037/0021-9010.67.3.306
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in personality traits of female and male Master of Business Administration students.

Abstract: The validity of the assumption that females do not have the personality traits commonly assumed to be characteristic of senior managers was investigated. Three personality measures were used to test 71 female and male Master of Business Administration (MBA) students: Sixteen Personality Factor Questionnaire, California Personality Inventory, and Rathus Assertive Inventory. The results showed that female and male MBA students did not generally differ on most measures of personality. An observed difference was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…Maccoby and Jacklin (l974), based on their review of research, concluded that men are indeed more aggressive than women in a wide vafjety of situations. Steinberg and Shapiro (1982) found that male and female M.B.A. students did not differ on traditional aspects of personality as measured by Cattell's 16PF, the California Personality Inventory (C.P.I. ), or the Rathus Assertive Inventory.…”
Section: Sex Differencesmentioning
confidence: 87%
“…Maccoby and Jacklin (l974), based on their review of research, concluded that men are indeed more aggressive than women in a wide vafjety of situations. Steinberg and Shapiro (1982) found that male and female M.B.A. students did not differ on traditional aspects of personality as measured by Cattell's 16PF, the California Personality Inventory (C.P.I. ), or the Rathus Assertive Inventory.…”
Section: Sex Differencesmentioning
confidence: 87%
“…Furthermore, the use of MBA students as subjects constitutes a relatively conservative test of the gender differences issue. Students who pursue MBA degrees are particularly likely to be interested in upward mobility and previous research indicates that female MBA students tend to possess traits that are commonly associated with competent managers (Steinberg & Shapiro, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Hospitality thus appears to be like other predominantly female professions, such as teaching, where women deal with the day-to-day roles, but men organize, plan, direct and control (Crampton and Mishra 1999). In other words, women continue to populate corporations but rarely run them (Steinberg and Shapiro 1982). One of the reasons for this may be that women are making choices that do not lead to senior positions.…”
Section: The Workforce Experiences Of Men and Womenmentioning
confidence: 95%